Conflict Resolution Strategies among Adolescent Victims of Sexual Dating Violence: Emotional Dependence, Regulation, and Social Support - Tatiwakeng, Rigel Jendrico; Huwae, Arthur (Journal of Psychological Perspective, 2025)
Sexual dating violence (SDV) is a global public health concern affecting a significant proportion of adolescents, with prevalence estimates ranging from 20% to 50% worldwide and disproportionately impacting young women. In Indonesia and other Southeast Asian contexts, disclosure remains limited due to stigma and cultural barriers, leaving many adolescents isolated in unsafe relationships. Against this backdrop, this study aimed to explore how adolescent victims of SDV navigate conflict resolution within their intimate relationships and identify the psychological, interpersonal, and social factors shaping their strategies. Using a qualitative instrumental narrative design, five adolescent females aged 15–22 who had experienced SDV and received at least one year of psychosocial support were recruited through purposive sampling. Data were collected via semi-structured interviews and field observations and analyzed thematically using Braun and Clarke’s framework. The findings revealed four key themes: (1) reliance on withdrawal as the most frequent conflict resolution strategy, (2) the entrapment of emotional dependence counterbalanced by gradual growth in regulation skills, (3) conflict involvement characterized by cycles of escalation and gaslighting, and (4) the pivotal role of social and emotional support in resilience and recovery. The study highlights that conflict resolution in SDV contexts is less about repairing relationships and more about survival, agency, and dignity, offering theoretical reframing and practical implications for trauma-informed interventions.